PENYEMPROTAN DISINFEKTAN UNTUK MENCEGAH COVID-19 DI DESA SUKAHARJA - Ryan Pradipto Ramadhan; Syaiful Syaiful; Asri Kusuma Wardhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
It is known to cause respiratory tract infections in humans ranging from coughs and colds to more serious ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). This disease can spread through small droplets from the nose or mouth when coughing or sneezing. The droplets then fall on objects around them. Then if someone else touches an object that has been contaminated with the droplets, then that person touches their eyes, nose or mouth (facial triangle), then that person can be infected with COVID-19. The spread of the COVID-19 virus is increasing rapidly through droplets of saliva or out of the nose when the infected person coughs or sneezes. However, there are still very few people around the village of Sukaharja Rt04/02 (temporary respiratory protective equipment) when doing activities outside the home considering. Therefore, it is necessary to understand that compliance with health protocols must be implemented as an effort to break the chain of transmission of COVID-19. Based on these problems, the author conducted community service through the SEMI OFFLINE KKN UIKA BOGOR 2021 activity (Joint Real Work Lecture Against Covid-19 UIKA BOGOR 2021). The Group Activity carried out in order to prevent the spread of COVID-19 was to distribute health equipment such as masks and hand sanitizers to the people of Sukaharja Village RT 04/02 Bogor Regency.